PENINGKATAN KINERJA KARYAWAN BERDASARKAN PRESPEKTIF PRAKTEK STRATEGI MANAJEMEN SUMBER DAYA MANUSIA PADA PT. ARTHA GUNUNG BATU DI DESA ANDEO - Muh. Adran; Asrip Putera; La Ode Bahana Adam; Abdul Razak Yusuf; Enny Wati (Jurnal Manajemen dan Kewirausahaan, 2022)
The purpose of this study was to determine the practice of human resource management in employee recruitment at PT. Artha Gunung Batu and to find out human resource management strategies in an effort to develop human resources to improve employee performance at PT. Artha Gunung Batu in Andeo Village, Lasolo District, North Konawe Regency. The data analysis technique used a qualitative approach with a descriptive method. The location of this research at PT. Artha Gunung Batu in Andeo Village, Lasolo District, North Konawe Regency.  The results of this study indicate that the recruitment process has been in accordance with recruitment procedures in general using the decision theory method of recruitment, for employee selection applying application letter selection, interviews 1 and 2, acceptance decisions and placement of employees who pass the selection. Human resource development to improve employee performance uses formal development where the development process is education and training for old and new employees.